CREATION OF MULTIMEDIA APPLICATIONS USING CLOUD TECHNOLOGIES FOR THE EDUCATIONAL PROCESS OF PRIMARY EDUCATION - Madiyor Palvannazirovich Masharipov; Gulchehra Zairovna Abdusamatova (Western European Studies, 2024)
This article details the creation and targeted use of cloud technologies, digital didactics, augmented reality (AR), virtual reality (VR) as well as multimedia technologies in the educational process today
Keywords: Аaugmented reality; virtual reality; Information Communication Technology; Information Technology